UPACARA ADAT KEMATIAN SAYUR MATUA SUKU SIMALUNGUN - Grace Shella S; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The research was conducted in Pematang Raya Village, Simalungun Regency with the aim of the reasons behind the family carrying out the traditional ceremony of death of sayur matua with toping huda-huda dance and describing the operation of social capital in the traditional ceremony. This research uses descriptive qualitative research methods. In the data using observation techniques, in-depth interviews and documentation. The results of the descriptive analysis show that the traditional ceremony of death of sayur matua is divided into two, namely riah tongah jabu and riah huta which are carried out by the kinship system tolu sahundulan and lima saodoran. The kinship system in question consists of tondong, sanina, suhut, tondong ni tondong, and boru mintori. The results of the observation analysis show that in carrying out the traditional ceremony of death of sayur matua, social action and social capital are needed. The social action behind the family holding a sayur matua death ceremony is a traditional action because they hold a habit on the basis that their ancestor teacher has passed down from generation to generation as an expression of gratitude and gratitude to God and parents who died perfectly because all their children were independent and have a family. The real action that exists in the traditional ceremony of death of sayur matua custom is in the form of social contact between individuals in the community which is carried out mutually and departing. The social capital that occurs in the traditional ceremony of death of sayur matua process is mutual trust, social networks, and norms owned by a person or group of organizations in order to achieve a common goal that shows the welfare of life and the cohesiveness of the community in Pematang Raya Village so that the traditional ceremony of the death of sayur matua is carried out with toping huda-huda dance smoothly and wisely.  Keywords : sayur matua, social action, social capital